Topics and trends in studies about teaching and learning english as a foreign language, efl, in kichwa-speaking students. a narrative review - Túquerres Perugachi, Talya Marisol (2021)
Conduct a narrative review to identify the topics and trends in studies about teaching and learning English as a foreign language with Kichwa-speaking students in the articles and thesis published between 2010 and 2020.